Reading and computational abilities as related to problem solving ability - Aribon, Lita C. (1979)
This study determined whether students' reading and comprehensional abilities are related to their word problem solving ability. Subjects in this study were 153 third year high school students from two schools in Pangasinan. The Pearson Product Moment Correlation was used. The findings of the study revealed that students' ability in solving linear equations was not related to their ability in identifying symbol translation of given word problems. The ability to solve linear equations, identify symbol translations of word problems and reading comprehension skill are closely associated and therefore, can be used to predict students' ability to solve word problems freely.